Perancangan Sistem Absensi Berbasis Web Pada Sekolah SMKS Wira Kesuma Jata - Dea Amallia (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Developing a web-based information system using the waterfall model, focusing on user needs analysis, design, development, testing, and system implementation. The results of the needs analysis indicate that users want a system that is easily accessible and efficient in data management. The design process produces an intuitive system design, while development is carried out using PHP and MySQL. System testing involves users to ensure functionality and stability, with the feedback obtained used for improvement. Implementation of the system in a real environment shows an increase in data management efficiency compared to the previous system. This study confirms the effectiveness of the waterfall model in developing information systems, although challenges in design flexibility still need to be considered. The results of this study are expected to provide a significant contribution to the development of web-based information systems that are more responsive to user needs.